Efektifitas Media Permainan Flashcard Dalam Meningkatkan Pengetahuan Kesehatan Reproduksi Anak Usia Prasekolah - Fathimah Kelrey; Rita Kombong; Tri N Hatala (Ilmiah Institut Citra Internasional, 2022)
Abstract Background, the implementation of flashcard media as a reproductive health learning medium for pre-school children is still very rarely applied by nurses in the community in schools to provide health education. The aim of this research is to increase the knowledge of pre-school age children about reproductive health through flashcards. Method, type of quantitative research with purposive sampling technique with statistical test dependent sample t-test (paired t test with (error level) of 5%. Results, flashcard media can help preschoolers in increasing children's knowledge about reproductive health. Conclusion, there is an increase in the level of knowledge after the treatment of health education for preschool age children using flashcard media. Suggestions, flashcard media can be used as learning media in early childhood.